Destroying the territory, weakening the body: an essay on food, illness and quebranto among the Tupinambá of Lower Tapajós in Northern Brazil - Fábio Zuker (Mana)
Abstract: This article explores the intricate connections between territorial degradation, bodily health, and the phenomenon of quebranto among the Tupinambá people of Lower Tapajós, Brazil. The Tupinambá attribute various health issues, physical debilitation, and diminished longevity to the consumption of urban-sourced foods, a pattern that correlates with the ongoing destruction of their ancestral lands. Since the mid-1950s, the encroachment of logging operations has progressively devastated Tupinambá territory, leading to an increasing dependence on external resources. The deterioration of the land is perceived as directly linked to the decline in human health; as the territory becomes “sick”, so too do its inhabitants. I engage with Tupinambá perspectives to analyze the impacts of territorial destruction on bodily vitality, particularly through the lens of quebranto, understood here as a form of corporeal malaise and a disruption in the commensal relationships that underpin kinship bonds - among people as well as between people and the land.